2007
DOI: 10.1253/circj.71.753
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Pulmonary Vein Antrum Isolation Using the "Large-Size" Lasso Catheter in Patients With Atrial Fibrillation

Abstract: lthough the efficiency of ostial pulmonary vein isolation (OPVI) to suppress the occurrence of atrial fibrillation (AF) is well established, 1 the relatively frequent recurrence of AF 2 and the appearance of pulmonary vein (PV) stenosis 3 have recently been highlighted as major limitations of this approach. Because the isolation of the PVs, together with their surrounding tissue, might overcome these problems, at least in part, several approaches using linear ablation techniques, such as circumferential linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 33 publications
0
57
0
Order By: Relevance
“…[1][2][3][4] To improve the clinical outcome, additional linear ablation to modify the substrate of AF has been proposed, 5-7 and we recently described an alternative approach of complete isolation of the posterior left atrium (LA), including all the PVs, for treating AF, namely the Box isolation. 8 However, this procedure is technically challenging because of variant atrial conductions, incomplete lesion lines or recovered conduction gaps being proarrhythmic.…”
mentioning
confidence: 99%
“…[1][2][3][4] To improve the clinical outcome, additional linear ablation to modify the substrate of AF has been proposed, 5-7 and we recently described an alternative approach of complete isolation of the posterior left atrium (LA), including all the PVs, for treating AF, namely the Box isolation. 8 However, this procedure is technically challenging because of variant atrial conductions, incomplete lesion lines or recovered conduction gaps being proarrhythmic.…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8] Using the Short-Form-36 questionnaire (SF-36), some previous reports showed a significant improvement in the QOL following the CA in patients with AF. 9,10 In this study, we used a questionnaire specific for AF, and assessed the clinical course of the QOL after the CA over a 6-month follow-up period in patients with both paroxysmal and chronic AF.…”
mentioning
confidence: 99%
“…We demonstrated that PVI was highly effective and safe in AF patients with a Brugada ECG, similar to other patients with idiopathic AF. [4][5][6][7][8]12 These findings suggest that PVI is a potential first-line therapy for symptomatic AF in patients with a Brugada ECG.…”
Section: Discussionmentioning
confidence: 84%